Study of path loss for ground based communication in military UHF band - Mao, Xiao Hong (2013)
Path loss along the Line-of-Sight and the Non Line-of-Sight routes in an urban environment are examined for the application of urban warfare in the military UHF band. Based on the experimental results, frequency dependency of the path loss, the path loss exponent and the corner loss are studied.